Effectiveness of Call Platforms (Quizlet, Bamboozle, Kahoot) in Motivating Teenage EFL Learners (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
It is increasingly important for second language teachers to develop stronger literacy in selecting and integrating effective technological learning platforms into their regular classroom practices. Prior studies suggest that when learners are supported with appropriate technology-enhanced tools, they tend to demonstrate greater engagement and sustained enjoyment in the learning process. This small-scale library research sought to explore the advantages of using Kahoot as an instructional medium in contemporary EFL settings. To achieve this goal, the researcher conducted a thematic analysis of findings drawn from 30 journal articles focusing on Kahoot-based instruction. This approach enabled the researcher to generate clearer insights by organizing the results into shared thematic categories. Two primary conclusions emerged: (1) Kahoot supports EFL learners in developing comprehensive foreign language proficiency, and (2) learners experience a more positive and motivating learning atmosphere when Kahoot is incorporated. The study also offers several recommendations to guide future research on the pedagogical benefits of technology-enhanced learning tools in diverse EFL classroom contexts.